2020
DOI: 10.3847/1538-4357/ab76cb
|View full text |Cite
|
Sign up to set email alerts
|

The HSC-SSP Transient Survey: Implications from Early Photometry and Rise Time of Normal Type Ia Supernovae

Abstract: With a booming number of Type Ia supernovae (SNe Ia) discovered within a few days of their explosions, a fraction of SNe Ia that show luminosity excess in the early phase (early-excess SNe Ia) have been confirmed. In this article, we report early-phase observations of seven photometrically normal SNe Ia (six early detections and one deep non-detection limit) at the COSMOS field through a half-year transient survey as a part of the Hyper Suprime-Cam Subaru Strategic Program (HSC SSP). In particular, a blue ligh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…They also note however that the fraction of SNe Ia with an excess is highly dependent on the SN subclass. Finally, Jiang et al (2020) present a handful of young SNe Ia observed as part of the HSC-SSP survey and estimate an early excess rate of ∼14% based on power-law fits to the early light curve.…”
Section: Comparisons With Previous Estimates Of the Early Excess Ratementioning
confidence: 99%
“…They also note however that the fraction of SNe Ia with an excess is highly dependent on the SN subclass. Finally, Jiang et al (2020) present a handful of young SNe Ia observed as part of the HSC-SSP survey and estimate an early excess rate of ∼14% based on power-law fits to the early light curve.…”
Section: Comparisons With Previous Estimates Of the Early Excess Ratementioning
confidence: 99%
“…Excess emission in the early light curve has been reported in a number of SNe Ia (Cao et al 2015;Marion et al 2016;Hosseinzadeh et al 2017a;Jiang et al 2018;Dimitriadis et al 2019a;Shappee et al 2019;Li et al 2019b). Al-ternatively, these early light curve features may be associated with mixing of radioactive 56 Ni (Piro & Morozova 2016;Miller et al 2018;Magee et al 2018;Jiang et al 2020;, He-shell detonation (Jiang et al 2017;Maeda et al 2018;Polin et al 2019;Siebert et al 2020), or circumstellar material interaction in DD scenario (Levanon & Soker 2017. Meanwhile, other studies have searched for narrow Hα/He emission lines in nebular phase spectra as a characteristic signature of the SD scenario (Marietta et al 2000;Mattila et al 2005;Pan et al 2010;Leonard 2007;Pan et al 2012;Liu et al 2012Liu et al , 2013Lundqvist et al 2013Lundqvist et al , 2015Shappee et al 2018;Graham et al 2015;Maguire et al 2016;Botyánszki et al 2018;Sand et al 2018Sand et al , 2019Shappee et al 2018;Dimitriadis et al 2019b;Holmbo et al 2019;Tucker et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Equation of State Supernova Cosmology Experiment program found about 200 SNe Ia with redshifts from 0.1 to 0.8 using the 4-meter CTIO Blanco telescope during its 2002-2008 running [30,31]. With the Hubble Space Telescope and the Subaru Hyper Suprime-Cam, the redshifts of discovered SNe Ia have been up to above 1.5 [10,[32][33][34][35]. On the other hand, several supernova surveys are designed to catch the nearby supernovae to investigate their physical nature.…”
mentioning
confidence: 99%